Earthquake sensitivity to tides and seasons: theoretical studies. Issue 2 (18th February 2021) - Pétrélis, François; Chanard, Kristel; Schubnel, Alexandre; Hatano, Takahiro
Abstract: We investigate theoretically the effects of periodic-in-time modulations on the properties of earthquakes. To wit, we consider successively the one dimensional Burridge–Knopoff (BK) model and the two dimensional Olami–Feder–Christensen (OFC) model. Each model is modified to take into account either a modulation of normal stress or of shear stress acting on a fault. Despite the differences between the BK and the OFC model, several results are observed in both models. In particular, we observe that earthquake occurrences correlate with stress modulation. The correlation is strongly dependent on parameters such as the type of modulation, its frequency and amplitude, and in some cases on the magnitude of the considered earthquakes.